THE EFFECTIVENESS OF TEAM ASSISTED INDIVIDUALIZATION LEARNING MODEL WITH REALISTIC MATHEMATICS APPROACH ON MATHEMATICAL PROBLEM-SOLVING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Winda Nur Akhadya; Ariyadi Wijaya (Universitas Negeri Yogyakarta, 2017)
This study aims to determine the effectiveness of Team Assisted Individualization learning model with realistic mathematics approach on mathematical problem-solving ability of Junior High School students. This research is quasi experiment with pretest posttest control group design. The subjects are 64 students from 3 Godean Junior High School which consist of class VIII F as the experimental class using Team Assisted Individualization learning model with realistic mathematics approach and class VIII D as the control class using expository learning model with deductive approach. Instrument that used are learning observation sheet and pretest-posttest items of mathematical problem-solving ability. Based on this research, it is conclude that Team Assisted Individualization learning model with realistic mathematics approach effective to the mathematical problem-solving ability of junior high school students. Furthermore Team Assisted Individualization learning model with realistic mathematics approach is more effective than expository learning model with deductive approach to the mathematical problemsolving ability of Junior High School students.